2010
DOI: 10.1179/030192310x12683045806062
|View full text |Cite
|
Sign up to set email alerts
|

Flow pattern in ingot during mould filling and its impact on inclusion removal

Abstract: A two-dimensional non-steady state computational fluid dynamic model was employed to gain a basic understanding of the flow in the ingot during casting. The surface velocity was found to be affected by the inlet angle and was found to vary with the casting level. The information of surface velocity was related to the probability of the inclusion removal. Water model experiments were also conducted to help the understanding. The model calculation revealed the same trends as the results of water model experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…For manganese the calculated values correlate very well with the measured ones, whereas for carbon the value differs clearly at the top of the ingot. This difference could be caused by the fact, that pickup of carbon from the insulation and the covering powder is not taken into account [8]. Also, the results for the high-alloyed element chromium varied along the centreline.…”
Section: Resultsmentioning
confidence: 99%
“…For manganese the calculated values correlate very well with the measured ones, whereas for carbon the value differs clearly at the top of the ingot. This difference could be caused by the fact, that pickup of carbon from the insulation and the covering powder is not taken into account [8]. Also, the results for the high-alloyed element chromium varied along the centreline.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be achieved by properly design the running system, in particular the nozzle angle. Different authors have already shown the advantages of using a divergent nozzle, also with the addition of a swirl [ 18 , 20 , 27 , 28 ]. In this case, the filling should be strongly improved by increasing the inlet nozzle angle and by adding a shock absorber at the end of the horizontal channel.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these inclusions are hard to remove from liquid steel, as the separation time is limited. Thus, many investigations have been performed to find ways to eliminate or reduce the formation of inclusions that originate from the mold flux.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a 25 ° angle of the inlet nozzle can reduce the risk of slag entrapments, leading to an almost flat rising surface and low surface velocities. Ragnarsson also investigated the opening angle in an ingot casting process where both water model experiments and numerical simulations were performed with a large range of opening angles. Their findings indicated that the inlet angle of 5° used in the industry was a good alternative with respect to the inclusion removal.…”
Section: Introductionmentioning
confidence: 99%